2012
DOI: 10.3765/bls.v38i0.3343
|View full text |Cite
|
Sign up to set email alerts
|

Logical Complexity in Morphological Learning: effects of structure and null/overt affixation on learning paradigms

Abstract: <p>This paper considers a morphological analogue of a psychological experiment on learning categories with the structure of Boolean connectives AND, OR, and XOR (exclusive OR). This experiment will test the effects of logical structure and the presence of null/overt affixes on paradigm complexity. The results are partially consistent with the previous psychological studies, however, they also differ in several ways from analogous non-linguistic experiments. At this point, it is unclear exactly what facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 9 publications
(8 reference statements)
0
8
0
1
Order By: Relevance
“…Russian learners show faster learning of the diminutive compared to Serbian learners (Savickienė, Kempe, & Brooks, ; Seva et al, ). While systematic morphological patterns are typically learned faster and with fewer errors than languages (MacWhinney, ; Pertsova, ; Slobin, ), these systematic patterns may help the learner find the more general morphological structure of the native language. This idea is also capitalized in Albright and Hayes' () model of morphology learning, in which the learner searches for “Islands of Reliability,” small cases where rules appear to be exceptionless.…”
Section: Morphophonologymentioning
confidence: 99%
See 1 more Smart Citation
“…Russian learners show faster learning of the diminutive compared to Serbian learners (Savickienė, Kempe, & Brooks, ; Seva et al, ). While systematic morphological patterns are typically learned faster and with fewer errors than languages (MacWhinney, ; Pertsova, ; Slobin, ), these systematic patterns may help the learner find the more general morphological structure of the native language. This idea is also capitalized in Albright and Hayes' () model of morphology learning, in which the learner searches for “Islands of Reliability,” small cases where rules appear to be exceptionless.…”
Section: Morphophonologymentioning
confidence: 99%
“…For example, languages are more likely to show syncretism in the dual compared to the singular. Several learning studies have shown support for the organizational structure of syncretism as a way of supporting learning (Finley & Wiemers, 2015;Pertsova, 2011Pertsova, , 2012. When syncretism resulted in the neutralization of a category, participants were more likely to learn the morphological endings of the language than when syncretism resulted in no category neutralization (Finley & Wiemers, 2015).…”
Section: Morphological Categories and Inflectional Paradigmsmentioning
confidence: 99%
“…The implications of these results are manifold. First, they ratify the relevance of naturalness and semantic similarity in grammatical (and morphological) architecture (Jakobson 1936;Bierwisch 1967;Baerman et al 2005;Pertsova 2014), a fact which has been recently challenged. Thus, for example, (Blevins forthcoming) suggests that "the contrast between 'natural' and 'unnatural' classes appears to reflect a priori assumptions about descriptive 'economy' and 'naturalness' which have never been shown to be relevant to language structure, acquisition or use."…”
Section: A Naturalness Gradient In Paradigmatic Splitsmentioning
confidence: 91%
“…Although the literature exploring a bias toward similarity-based structure in language learning has long focused on words (and in particular on content words), such a bias could also be at play during the learning of morphological paradigms (Johnson et al, 2021;Maldonado & Culbertson, 2021;Nevins, 2015;Nevins et al, 2015;Pertsova, 2014).…”
Section: Morphological Learningmentioning
confidence: 99%
“…(Cysouw, 2003;Pertsova, 2007). There is a growing body of literature which aims to explain this cross-linguistic tendency towards naturalness from constraints in language learning (Johnson, Gao, Smith, Rabagliati, & Culbertson, 2021;Maldonado & Culbertson, 2021;Nevins, 2015;Nevins, Rodrigues, & Tang, 2015;Noyer, 1992;Pertsova, 2011Pertsova, , 2014. These studies suggest that adults find it easier to learn patterns of syncretism with shared values.…”
Section: Introductionmentioning
confidence: 99%